The Church Historians Who made the First Amendment What it is Today - Drakeman, Donald L. (Religion and American culture, 2007)
Thomas Jefferson and James Madison are frequently identified as the framers of the religion clauses in the First Amendment, thus making their efforts to establish religious freedom in colonial Virginia relevant to the Constitution's meaning. This interpretive approach first appeared in a Supreme Court opinion in 1878 when Chief Justice Morrison Waite applied the religion clauses to the case of a Mormon official prosecuted under a federal antipolygamy law. For historical background, Justice Waite studied books by church historians Robert Reid Howison and Robert Baylor Semple. There, he encountered narratives of the political activism of the Baptists and Presbyterians who, in conjunction with the efforts of Madison and Jefferson, were responsible for Virginia's statutory commitment to religious freedom. The Chief Justice then grafted Madison's Memorial and Remonstrance against Religious Assessments and Jefferson's now-famous “wall of separation” letter onto the Constitution's bare text, an emendation that has endured for well over a century. Church historians Semple and Howison, and the pivotal role they played in the foundation of First Amendment jurisprudence, have been essentially lost from the historiographical record of church-state relations in America, a situation this article seeks to remedy.